A MODEL OF THE INNOVATIVE AMBER CLUSTER AS A CENTRE OF COOPERATION OF AUTHORITIES - BUSINESS - SCIENCE - Gleb B. Trifonov; Yuriy N. Tsaregorodtsev; Victor M. Murov (Статистика и экономика)
A mechanism of forming an innovative amber cluster was developed, including structural interconnections of cluster partners,a package of basic innovative technologies, which will createa new value chain, new vacancies, provide contributions to theregional budget.A method of analytical estimation was suggested to assess cluster synergism of partners: authorities, business, science/education, culture, which reﬂects potential possibilities of thecluster model of region development.